Discovering diversity how the diverse values and beliefs of world religions are shaping our identity - Armstrong, Jocelyn (Pearson social studies, 2009)
Shaping a future -- New cultures, new religious faiths -- A multicultural nation -- Judaism's rites of passage -- Christianity's festivals -- Islam's way of life -- Hinduism's living stories -- Buddhism's ethics and meditation -- Sikhism's symbols -- The challenges of diversity -- Responding to the challenges -- Inquiry and discovery